Kefir grains as a starter for whey fermentation at different temperatures: chemical and microbiological characterisation - Londero, Alejandra (2012)
We report here a comparative analysis of the growth, acidification capacity, and chemical and microbiologic composition between kefir grains after 20 subcultures in whey at 20, 30, and 37 °C and the original kefir grains coming from milk along with a determination of the microbiological composition of the fermented whey as compared with that of traditional fermented milk. When fermentation was carried out repeatedly at 30 or 37 °C, kefir grains changed their kefir-like appearance, exhibited reduced growth rates, had a lower diversity of yeasts and water content, and a higher protein-to-polysaccharide ratio compared with the original kefir grains. In contrast, at 20 °C kefir grains could remain in whey for prolonged periods without altering their acidification capacity, growth rate, macroscopic appearance or chemical and microbiologic composition—with the only difference being a reduction in certain yeast populations after 20 subcultures in whey. At this incubation temperature, the presence of Lactobacillus kefiranofaciens, Lb. kefir, Lb. parakefir, Lactococcus lactis, Kluyveromyces marxianus, Saccharomyces unisporus, and Sac. cerevisiae was detected in kefir grains and in fermented whey by denaturing-gradient-gel electrophoresis (DGGE). In whey fermented at 20 °C the number of lactic-acid bacteria (LAB) was significantly lower (P< 0·05) and the number of yeast significantly higher (P< 0·05) than in fermented milk. Since the DGGE profiles were similar for both products, at this temperature the microbiologic composition of fermented whey is similar to that of fermented milk. We therefore suggest a temperature of 20 °C to preserve kefir grains as whey-fermentation starters.